Examining the Role of Microfinance Institutions in Enhancing Financial Inclusion and Economic Growth - Raut, Bin Bahadur (International Research Journal of MMC, 2025)
This study examines the role of microfinance institutions (MFIs) in enhancing financial inclusion and fostering economic growth. Employing a qualitative exploratory research design, the study relied on secondary data sourced from journal articles, books, reports from financial regulatory bodies, and relevant online databases. The findings indicate that MFIs play a crucial role in providing financial services to marginalized communities, promoting entrepreneurship, reducing income inequality, and stimulating economic activities. However, challenges such as high interest rates, limited outreach, and sustainability concerns persist. The implications of this study highlight the need for policy interventions to strengthen the effectiveness of MFIs through regulatory support, technological innovation, and capacity-building programs. These insights contribute to the broader discourse on financial inclusion and provide valuable recommendations for policymakers, financial institutions, and development agencies aiming to enhance economic participation among low-income populations.